Driving safety improves after individualized training: An RCT involving older drivers in an urban area. (18th August 2019) - Gagnon, S.; Stinchcombe, A.; Curtis, M.; Kateb, M.; Polgar, J.; Porter, M. M.; Bédard, M.
Abstract: Objective: This study aimed to reproduce the results of a previous investigation on the safety benefits of individualized training for older drivers. We modified our method to address validity and generalizability issues. Methods: Older drivers were randomly assigned to one of the 3 arms: (1) education alone, (2) education + on road training, and (3) education + on road + simulator training. Older drivers were recruited from a larger urban community. At the pre- and posttests (separated by 4 to 8 weeks) participants followed driving directions using a Global Positioning System (GPS) navigation system. Results: Our findings support the positive influence of individualized on-road training for urban-dwelling older drivers. Overall, driving safety improved among drivers who received on-road training over those who were only exposed to an education session, F(1, 40) = 11.66, P = .001 (26% reduction in total unsafe driving actions [UDAs]). Statistically significant improvements were observed on observation UDAs (e.g., scanning at intersections, etc.), compliance UDAs (e.g., incomplete stop), and procedural UDAs (e.g., position in lane). Conclusion: This study adds to the growing evidence base in support of individualized older driver training to optimize older drivers' safety and promote continued safe driving.